Cost-effectiveness of various referral pathways to identify advanced fibrosis among type 2 diabetes mellitus patients with metabolic dysfunction-associated steatotic liver disease in primary care setting in Malaysia - Wei Yoon Poh; Amirah Azzeri; Shamsul Mohd Zain; Rosmawati Mohamed; Kim Sui Wan; Xe Hui Lee; Maznah Dahlui; Fatiha Hana Shabaruddin (PLoS ONE, 2026)
Background and aim Most international guidelines recommend a two-step approach using the Fibrosis-4 index (FIB-4) and vibration-controlled transient elastography (VCTE) to identify advanced fibrosis, a key predictor of all-cause and liver-related mortality in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). However, VCTE is not available in most primary care settings in Malaysia, and there is scarce data on the cost-effectiveness of different approaches. This study evaluated the cost-effectiveness of three referral pathways for identifying advanced fibrosis among type 2 diabetes mellitus(T2DM) patients with MASLD. Methods We developed a decision-analytical model from the healthcare provider’s perspective, using 1,000 simulated patients to compare: (i) Current Practice (direct referral based on elevated alanine transaminase), (ii) Clinical Practice Guidelines (CPG) Pathway using FIB-4 single-cutoff 1.3, and (iii) FIB-4 dual-cutoffs (1.3,3.25) followed by a gamma-glutamyl transferase (GGT) test for indeterminate cases (Sequential FIB-4/GGT Pathway). Current practice served as the reference comparator. The primary outcomes were the average cost-effectiveness ratio (ACER) and the incremental cost-effectiveness ratio (ICER). Model parameters were mainly derived from local studies. Direct medical costs were reported in 2024 Malaysian Ringgit (MYR). Results Sequential FIB-4/GGT pathway had the lowest ACER at MYR930 per advanced fibrosis case identified, compared to MYR1,299 for current practice and MYR1,581 for the CPG pathway. Sequential FIB-4/GGT pathway was potentially more effective and less costly, demonstrating dominance over current practice with a cost savings of MYR2,911/additional advanced fibrosis case identified. CPG pathway was more effective and more costly than current practice, with an ICER of MYR3,785. Conclusions Sequential FIB-4/GGT pathway was cost-effective for identifying advanced fibrosis in T2DM patients with MASLD. This pragmatic approach could reduce tertiary care referrals, lower healthcare resource use and costs compared to current practice. CPG pathway was more effective than current practice, but incurred higher costs and required increased availability of VCTE within clinical practice.